The theater of refusal Black art and mainstream criticism : artists: Jean-Michel Basquiat, Renee Green, David Hammons, Ben Patterson, Adrian Piper, Sandra Rowe, Gary Simmons, Lorna Simpson, Carrie Mae Weems, Pat Ward Williams, Fred Wilson - Anastas, Rhea 1969-; Gaines, Charles; James, Jamillah 1980-; Stone, Eric Golo (The Brick, 2024)
"In 1993, at the University of California, Irvine, Charles Gaines and Catherine Lord mounted a category-breaking exhibition of Black artists from different generations, working across Fluxus, Conceptualism, assemblage, photography and installation. Challenging the racializing of Black artists’ work, the exhibition confronted the discourse around race difference in the United States by including excerpts of writing by art critics who had discussed the featured artists. On the 30th anniversary of this event, this publication reprints the eponymous 1993 volume documenting the show, which contained essays by Gaines, Lord and Berger, and the transcript of a roundtable of artists and writers. Reproducing images of the exhibition in color for the first time, this new edition augments the original publication with an essay by poet and scholar Fred Moten; recent conversations between Lord and Gaines; an interview with Gaines by Moten; and a new roundtable discussion moderated and edited by curator Jamillah James and Thomas (T.) Jean Lax."
Impressum: This book was organized on the occasion of the 30th anniversary of the publication "Theater of Refusal: Black Art and Mainstream Criticism", edited by Charles Gaines and Catherine Lord, and published by the Fine Arts Gallery, University of California, Irvine, in 1993. - Rückseite Titelblatt: Exhibiton schedule: University of California, Irvine, Fine Arts Gallery, April 8 - May 12, 1993; University of California, Davis, Richard L. Nelson Gallery, November 7 - December 17, 1993; University of California, Riverside, University Art Gallery, January 9 - February 27, 1994
Ausgabebezeichnung vom Schutzumschlag
Keywords: Geschichte 1993-2024; Rezeption; Nationalbewusstsein -- Motiv; Kunst; Ausstellung; Schwarze; USA; 1900-1999; African American art / 20th century / Exhibitions; Art noir américain - 20e siècle - Expositions; African American art; Art noir américain - États-Unis - Catalogues d'exposition; exhibition catalogs; Exhibition catalogs; Catalogues d'exposition; Ausstellungskatalog -- Fine Arts Gallery -- 08.04.1993-12.05.1993 -- Irvine, Calif.; Ausstellungskatalog -- Richard L. Nelson Gallery -- 07.11.1993-17.12.1993 -- Davis, Calif.; Ausstellungskatalog -- University Art Gallery -- 09.01.1994-27.02.1994 -- Riverside, Calif.